Early‐onset vitamin B6‐dependent epilepsy due to pathogenic PLPBP variants in a premature infant: A case report and review of the literature. Issue 1 (15th November 2020) - Heath, Oliver; Pitt, James; Mandelstam, Simone; Kuschel, Carl; Vasudevan, Anand; Donoghue, Sarah
Abstract: Vitamin B6 ‐dependent epilepsies are a heterogeneous group of disorders characterized by decreased availability of the active cofactor pyridoxal‐5′‐phosphate (PLP). While pathogenic variants in ALDH7A1 or PNPO genes account for most cases of these disorders, biallelic pathogenic variants in PLPBP have been shown to cause a form of early onset vitamin B6 ‐dependent epilepsy (EPVB6D). PLPBP is thought to play a role in the homeostatic regulation of vitamin B6, by supplying PLP to apoenzymes while limiting side‐reaction toxicity related to excess unbound PLP. Neonatal‐onset intractable seizures that respond to pyridoxine and/or PLP are a predominant feature of EPVB6D in humans. Unlike other causes of vitamin B6 ‐dependent epilepsies; however, a specific biomarker for this disorder has yet to be identified. Here we present data from a premature infant found to have pathogenic variants in PLPBP and propose that prematurity may provide an additional clue for early consideration of this diagnosis. We discuss these findings in context of previously published genotypic, phenotypic, and metabolic data from similarly affected patients.